Masyarakat Kalijeruk dalam Pelestarian Pertunjukan Ebeg - Nuzulul - Fadillah; Heri - Kurnia (Universitas Hamzanwadi, 2023)
The sophistication of technology and communication systems has had an impact on the high flow of globalization that has entered Indonesia. Not a few foreign cultural influences that enter are not in accordance with the cultural norms of the Indonesian nation. This is because people are more familiar with foreign cultures compared to native Indonesian culture. One of them is the traditional art of Ebeg as one of the noble heritages of the ancestors of the Indonesian people, which from now on is rarely found. A sense of belonging to the young people of Kalijeruk Village is needed for Ebeg art as an art that deserves to be upheld and becomes the pride of the community. This Ebeg art is widely displayed by people at festivals, celebrations, competitions and celebrations on certain days. The author discusses the preservation of Ebeg art using documentation and observation studies. Through literature review and observational notes, the data obtained was then collected, selected and presented in the discussion. As early as possible, the young people of Kalijeruk Village are introduced to Ebeg art and trained to play it so that they can continue the art that has been passed down from generation to generation as an intangible cultural heritage. The explanation presented is expected to be able to become a value of public awareness of the preservation of the Indonesian nation's traditional arts.